Age of onset moderates the effects of Vascular Risk Factors on Neurodegeneration, Blood-Brain-Barrier permeability, and cognitive decline in Alzheimer’s Disease - Chiara Giuseppina Bonomi; Caterina Motta; Martina Gaia Di Donna; Martina Poli; Marzia Nuccetelli; Sergio Bernardini; Nicola Biagio Mercuri; Giacomo Koch; Alessandro Martorana (Alzheimer’s Research & Therapy)
Abstract Background The role of Vascular risk factors (VRFs) in the progression of Alzheimer’s Disease (AD) and cognitive decline remains to be elucidated, with previous studies resulting in conflicting findings. The possible impact of age-specific mechanisms of resilience/vulnerability is an under addressed issue. We evaluated the association of VRFs with markers of amyloid deposition, neurodegeneration, and blood-brain-barrier (BBB) permeability (Albumin quotient, Qalb), stratifying patients into early-onset (< 65, EOAD), classic late-onset (65–75, cLOAD) and very late-onset (> 75, vLOAD), to evaluate the moderating effect of age of onset. Moreover, we explored the effects of VRFs on cognitive decline at one year follow-up (ΔMMSE). Methods For 368 patients with biologically confirmed AD, we computed eight risk factors in a composite measure of cumulative vascular risk (vascular score, VS). Stratifying patients according to age of onset, we regressed VS and main individual VRFs on p-tau/Aβ42, t-tau and Qalb, and used bootstrapped mediation analysis to test direct and indirect associations of VS with t-tau, using Qalb as mediator. In a subset of 105 patients, we performed multivariate backward regressions to assess the effects of sex, APOE, Qalb, VS, p-tau/Aβ42 and t-tau on ΔMMSE. Results VS was positively associated with CSF t-tau in more vulnerable groups burdened by more aggressive disease progression (EOAD: β = 0.256, p = 0.019) or aging (vLOAD: β = 0.007, p < 0.001). Conversely, in patients with classic age of onset VS was associated with higher BBB permeability (cLOAD: β = 0.173, p = 0.015), which simultaneously causes the decrease of CSF t-tau, as a possible resilience response. Cognitive decline was not associated with VS in any of the subgroups. Instead, it was affected by both higher CSF t-tau and increased Qalb values in those with very early or very late onset (EOAD and vLOAD), but by Qalb alone in patients with classic age of onset, where CSF t-tau levels might be buffered by BBB permeability. Conclusions Our results show that age of onset weighs on the heterogeneous effects played by VRFs in AD, which do not seem to have direct impact on cognitive decline. These findings stress the importance of a tailored patient-centered approach to the application of vascular prevention strategies in AD.